2018
DOI: 10.15809/irriga.2017v22n1p115-128
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência No Uso Da Água E Acúmulo De Matéria Na Batata-Doce Em Função De Lâminas De Irrigação

Abstract: Among the biological processes that affect the productivity of sweet potatoes, the water deficit stands out, and irrigation becomes an important technique to obtain higher agricultural yields.With the limited availability of water for agriculture and high energy costs, it is necessary to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…Highest estimate of WUE was equal to 64 kg ha -1 mm -1 , relative to the lowest ID, which is 58.9% higher than the WUE of 40 kg ha -1 mm -1 obtained with the highest ID (642 mm) and 44.8% higher than the WUE of 44 kg ha -1 mm -1 obtained with the ID of 567 mm, which guaranteed maximum physical yield of the crop. Such response can be explained by the capacity of the stomata to reduce their conductance to water vapor in response to the water deficit, promoting lower water loss per unit of carbon assimilation, thus improving water use efficiency in stressed plants (Silva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Highest estimate of WUE was equal to 64 kg ha -1 mm -1 , relative to the lowest ID, which is 58.9% higher than the WUE of 40 kg ha -1 mm -1 obtained with the highest ID (642 mm) and 44.8% higher than the WUE of 44 kg ha -1 mm -1 obtained with the ID of 567 mm, which guaranteed maximum physical yield of the crop. Such response can be explained by the capacity of the stomata to reduce their conductance to water vapor in response to the water deficit, promoting lower water loss per unit of carbon assimilation, thus improving water use efficiency in stressed plants (Silva et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the constant occurrence of water deficit in the Northeast region, irrigation is frequently used to cultivate zucchini, a practice that requires adequate management in order to make the most of its potential benefits (Carvalho et al, 2011;Oliveira et al, 2012), avoiding negative effects caused by either water deficit (Delazari et. al., 2017) or water excess (Viana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The fresh matter of the aerial part superiority expresses the response of greater water content in the soil, and, therefore, the greater state of water energy in the leaves and turgor of the guard cells, with a positive reflection in biomass production by plants, in general (TAIZ et al, 2017), including sweet potato (DELZARI et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Almeida et al (2015) and Cui et al (2020) concluded that the water deficit inhibits crop photosynthesis, growth and production. This situation expresses the dependence of agricultural production systems on irrigation, in the semiarid world, and requires the adoption of water management strategies in order to obtain sustainable agricultural yields to guarantee food availability, given the growing global concern (SOUZA et al, 2016;DELZARI et al, 2017;EL-FOTOH et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, as hortaliças têm seu desenvolvimento bastante influenciado pelas condições de água do solo, onde a deficiência hídrica é, normalmente, o fator mais limitante à obtenção de produtividades elevadas e produtos de boa qualidade, entretanto o excesso é considerado prejudicial (SANTANA et al, 2016). Assim, a irrigação surge como uma importante técnica para a obtenção de maiores níveis de produção das culturas agrícolas (DELAZARI et al, 2017).…”
unclassified